Một vài khía cạnh thuật toán của các kỹ thuật lọc và làm rõ đường biên trong xử lí ảnh - Kiếm, Hoàng Văn; Phước, Trần Vĩnh (Journal of Computer Science and Cybernetics, 2016)
This paper presents an analysis of the complexity of  traditional filtering and sharpening algorithms in image processing. After analyzing their efficiency and  computation complexity, we prose an approach based on the the use k-values information of ordered set for restoring image with high quality and reducing the computation.